Anestesi Regional Dengan Teknik Combined Spinal–Epidural pada Nefrolitotomi: (Laporan Kasus) - Siti Sarah Amanda; Dicky Noviar (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Combined spinal epidural (CSE) is a regional anesthesia technique that combines the rapid onset of spinal anesthesia with the flexibility and prolonged analgesia of epidural anesthesia, making it a valuable option for major surgery in elderly patients with comorbidities. We report a case of a 76-year-old man with ASA physical status III diagnosed with multiple nephrolithiasis accompanied by bilateral hydronephrosis, who underwent open right nephrolithotomy under CSE anesthesia. The patient had a history of hypertension and mild renal function impairment, placing him at increased perioperative risk. Intraoperatively, hemodynamic parameters remained stable without significant hypotension, vasopressor requirement, or conversion to general anesthesia. Estimated blood loss was approximately 500 mL and was managed with crystalloid replacement without transfusion. Prophylactic antibiotic and adjuvant medications were administered according to surgical standards. Postoperatively, the patient was monitored in the ICU with stable vital signs and adequate pain control achieved through continuous epidural analgesia. This case highlights that CSE can be a safe and effective anesthetic approach for open nephrolithotomy in selected high-risk geriatric patients, providing satisfactory hemodynamic stability and postoperative recovery.